Synthesis of green nano iron particles (GnIP) and their application in adsorptive removal of As(III) and As(V) from aqueous solution - Prasad, Kumar Suranjit; Gandhi, Pooja; Selvaraj, Kaliaperumal (Applied Surface Science, 2014)
{The present study reports a new approach to synthesise nano iron particles using leaf extract of Mint (Mentha spicata L.) plant. The synthesised GnIPs were subjected to detailed adsorption studies for removal of arsenite and arsenate from aqueous solution of defined concentration. Iron nanoparticles synthesised using leaf extract showed UV-vis absorption peaks at 360 and 430 nm. TEM result showed the formation of polydispersed nanoparticles of size ranging from 20 to 45 nm. Nanoparticles were found to have core-shell structure. The planer reflection of selected area electron diffraction (SAED) and XRD analysis suggested that iron particles were crystalline and belonged to fcc (face centred cubic) type. Energy-dispersive X-ray analysis (EDAX) shows that Fe was an integral component of synthesised nanoparticles. The content of Fe in nanoparticles was found to be 40%, in addition to other elements like C (16%), 0 (19%) and Cl (23%). FT-IR study suggested that functional groups like NH
Keywords: Adsorption; Arsenate; Arsenite; Iron nanoparticles; kinetics; M. spicata L.

Synthesis of water soluble CdS nanoparticles and study of their DNA damage activity - Prasad, K. S.; Amin, T.; Katuva, S.; Kumari, Madhu; Selvaraj, Kaliaperumal (Arabian Journal of Chemistry, 2017)
This study reports a novel method for preparation of water soluble CdS nanoparticles using leaf extract of a plant, Asparagus racemosus. The extract of the leaf tissue which worked as a stabilizing and capping agent, assisted the formation of nanoparticles. Nanoparticles were characterized using a UV–vis spectrophotometer, Photoluminescence, TEM, EDAX, XRD and FT-IR. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of spherical, polydispersed, crystalline, CdS of diameter ranging from 2 to 8 nm. X-ray diffraction studies showed the formation of 1 1 1, 2 2 0 and 3 1 1 planes of face-centered cubic (fcc) CdS. EDAX analysis confirmed the presence of Cd and S in nanosphere. The cytotoxicity test using MTT assay as well as DNA damage analysis using comet assay revealed that synthesized nano CdS quantum dots (QDs) caused less DNA damage and cell death of lymphocytes than pure CdS nanoparticles.